Biomarkers in alcohol use disorder - Tekkeşin, Nilgün (Journal of Dependence, 2024)
In recent years, significant advances have been made in the biological assessment of heavy alcohol use. These advances include the development of new laboratory tests, the formulation of algorithms to combine results across multiple measures, and broader applications of biomarkers in alcohol use disorder treatment and research. Alcohol drinking is arguably the oldest social habit worldwide, is highly prevalent in many cultures, and contributes significantly to the global burden of health and social problems. Although many studies have been published on scientific platforms about biomarkers for the detection of alcohol use disorder, a few basic questions remain. First of all, dose-response relationships need to be specified. In screening for alcohol problems, there may be some “questioning of suspicion” before a particular biomarker is used. This questioning of suspicion involves an inadequate self-report or equivocal findings on clinical examination. Findings: While biomarkers are subject to many of the usual psychometric issues regarding validity and reliability, the considerations for their evaluation are different. Instead, the main criteria for evaluating biomarkers are; Criterion validity is concerned with stability, test-retest consistency, and reliability in clinical interpretation. This performance information is also valid for new reagents such as CDT (Carbonhydrate Deficient Transferrin), especially for which fully automated testing procedures have been developed. With the use of biomarkers, the analytical approach in clinical decision-making becomes clearer. Therefore, it is critical to measure the increasing information value of biomarkers and to search for effective algorithms. This article specifically addresses general issues regarding biomarkers used as diagnostic-screening tests.